PENERAPAN EVIL TWIN DETEKTOR DALAM PENDETEKSIAN PENGGANGGU JARINGAN NIRKABEL PADA USER - Peniarsih, Peniarsih (Universitas Dirgantara Marsekal Suryadarma, 2017)
Nowadays, wireless networking facilities are provided in public places such as fast food restaurant, airports, hotels, campuses and are an attraction for users to use them. The wireless network provided uses an open authentication system and web-based authentication as the second layer used by customers to identify themselves according to the service they have before they can connect to the internet or WiFi Hotspot is a frequently used name. However, unnoticed by the user, it can be utilized by parties who are not entitled to attack and disturb. One of the attacks on wireless networks is the evil twin attack, given the ease in creating it by only duplicating the existing wireless network configuration and forcing users to move to the evil twin network because the installation tends to be closer to the victim's location. Administrator-based detection is one solution that is implemented but has a dependency on the availability of network administrators and supporting devices. To assist users in detecting disturbances, this research proposed client-based evil twin detection that utilizes Medium Access Control (MAC) address data and automatic configuration information provided by a Dynamic Host Configuration Protocol (DHCP) server on a wireless network. Shell programming on the Linux operating system is used to implement the solution. Keywords: Evil Twin Attack, Hotspot WiFi, WiFi Security